Real-Time Monitoring of a PV-Based Solar Power System in a South-Western Nigerian City using LABVIEW - Lawal, Muyideen Olalekan; Olaniran, Olakunle; Olaniyi, Babatunde Zaccheus (Universitas Muhammadiyah Magelang, 2023)
Understanding what is obtainable from a PV-based solar power system is key to proper sizing of the system. The parameters that are important are the time range available for energy delivery from the panel, time at maximum charging current and the available charging current. To determine these parameters, this work sets up a complete PV-based solar system that was interfaced with National Instrument myDAQ (NI myDAQ) and LABVIEW program for data collection for a specific period of time. The collection periods were nineteen (19) days which cuts across days in September to November. The data collected are the time stamps, charging current and battery voltage. The study outcome reveals that the average time range for the delivery of energy from the solar module for those periods are 7:24 am to 5:31 pm. The average time at maximum charging current is 12:32 pm. The maximum charging current recorded is 0.509 A, which is 89.3 percent of the panel’s current at maximum power.